STRATEGI PEMASARAN PRODUK BARU - Sarjono, Bambang (Orbith, 2015)
In the marketing strategy a new product can be conducted optimally with a good strategy. The newproduct effected to product selling target is achieved an increasing of product selling volume. Thisresearch conducted to know effect of marketing strategy consisting of product strategy, price strategy,promotion strategy and distribution strategy interest of consumer buying of a new product both ofsimultaneously or partially. Research approach that used is explanatory and use survey method withquantitative data type that try to relate some independent variable: product strategy, price strategy,promotion strategy and distribution strategy to dependent variable of increasing selling , to open of intervariablephenomena.Theory building to support research hypothesisexplains that there is relation and influence of marketing strategy to interest of consumer buying to a new product. From result of research found, that: there is positive influence and significant between product strategy, price strategy, promotion strategy and distribution strategy to the increasing selling of a new product both of simultaneously or partially. In the other hand, discover from consumer processing assessment of marketing activity through the product strategy price strategy is already good while promotion strategy and distribution strategyrelatively low need to be repaired and improved by company. From the prediction model is shown that influence of the independent variable to the dependent variable are promotiont strategy, distribution strategy, product strategy and price strategy.